Knowledge economy and sustainable economic development : a critical review - Nguyễn, Thanh Tuyền (Knowledge & information., 2010)
In this book, the author focuses on the intersection of two major bodies of policy and practice: knowledge economy and ICTs on one hand, and sustainable economic development on the other. It aims to provide a broad-ranging account of the social and economic terrain demarcated by this intersection in order to reach conclusions and offer guidelines for policy development. Although based on the case of a developing country (Vietnam) its analyses, arguments and conclusions are of universal relevance. Key features comprehensive picture of a society from the perspective of knowledge for development Intersection of ICTs (Information and Communications Technology), knowledge, and sustainable economic development Can be used in courses of sociology, political economy, development economics, knowledge economics, information and telecommunication technology, sustainable development, and public administration. --From publisher's description.